1990
DOI: 10.1107/s0108270189008802
|View full text |Cite
|
Sign up to set email alerts
|

Structures of two isomeric hydroxamic acids: N-methyl-p-toluohydroxamic acid (MTH) and N-(4-methylphenyl)acetohydroxamic acid (MPA)

Abstract: . The hydroxamate group in each compound assumes the trans conformation as observed in other secondary hydroxamic acids. The interchange of the C and N substituents influences the planarity and dimensions (C---~O, C--N bonds) of the hydroxa, mate moiety. In MTH the hydroxamate group shows significant deviation from planarity; the r.m.s, deviation of the four atoms, @--N--O(H), is 0.094 A, whereas in MPA it is only 0.004A. This nonplanarity is due largely to out-of-plane bending at N, XN = 23"9 (1) °, as compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…The E - and Z -isomers of hydroxamates may have different nucleophilicities and basicities, which complicates comparisons of rate constants in different media, including micelles. Polar, hydroxylic solvents increase the Z : E ratio, as do micelles. , …”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The E - and Z -isomers of hydroxamates may have different nucleophilicities and basicities, which complicates comparisons of rate constants in different media, including micelles. Polar, hydroxylic solvents increase the Z : E ratio, as do micelles. , …”
mentioning
confidence: 98%
“…Hydroxamate ions are α-effect nucleophiles; i.e., they are better nucleophiles than predicted by Bronsted relations between nucleophilicity and basicity. , However, hydroxamic acids and their anions, which are α-effect nucleophiles, exhibit amide-like geometrical isomerism and the E : Z ratio depends on structure, solvent composition, and incorporation in association colloids. , Insofar as E and Z isomers may differ in their nucleophilicities, this isomerism complicates analyses of relations between structure and reactivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2) with that of the corresponding N-methyl-4-methylbenzohydroxamic acid [18] and 1e (Fig. 1) revealed some significant differences in bond lengths.…”
Section: Methodsmentioning
confidence: 82%
“…Nevertheless, the (N,O), (N,N), and bridging bis‐chelating modes forming metallocrowns are also known . The acetohydroxamic acid and a number of C‐ and N‐substituted hydroxamic acids studied by X‐ray crystallography have shown that the nature of the C‐ and N‐substituents influence the stability of the metal hydroxamato/imato complex . The hydroxamic acids with electron donating substituents (NH 2 , OH) at the aromatic ring form more stable complexes by increasing the localized negative charge on the coordinating oxygen atoms while those with electron withdrawing substituents (NO 2 , F, Cl) exhibit higher biological activity …”
Section: Introductionmentioning
confidence: 99%